Proton beam irradiation of uveal melanoma involving the iris, ciliary body and anterior choroid without surgical localisation (light field). Issue 4 (21st December 2020) - Oxenreiter, Monica M; Lane, Anne M; Aronow, Mary Beth; Shih, Helen; Trofimov, Alexei V; Kim, Ivana K; Gragoudas, Evangelos S
Abstract : Aims: To assess treatment outcomes after proton beam irradiation (PBI) without surgical localisation of uveal melanomas involving the iris, ciliary body and anterior choroid. Methods: Retrospective chart review of 125 patients evaluated at Massachusetts Eye and Ear and treated with PBI using a light field set-up without localisation surgery between November 1975 and April 2017. The tumours were characterised as follows: iris (n=18, 14.4%), ciliary body (n=12, 9.6%), iridociliary (n=58, 46.4%), ciliochoroidal (n=24, 19.2%) and iridociliochoroidal (n=13, 10.4%). The tumours were measured by transillumination and ultrasonography before treatment. Tumours with posterior margin located less than two disc diameters from the ora serrata were treated using the light field technique. Patient outcomes after PBI were evaluated. Results: Most patients had good vision at the time of tumour diagnosis (69.6% had baseline visual acuity (VA) of ≥20/40). Median VA at last follow-up (median follow-up: 72.1 months) was 20/63. Recurrences occurred in 12 patients (9.6%) at a median time of 4.0 years post-treatment. Recurrences were treated by repeat PBI (n=5) or enucleation (n=7). Secondary enucleation was performed in 18 patients (14.4%), and 61.1% of these were due to complications. Neovascular glaucoma (NVG) developed in 21 patients (16.8%). Of seven patients who developed NVG after anti-vascular endothelial growth factor (anti-VEGF) therapies became available, five were treated with intravitreal Avastin injections (23.8% of patients with NVG). Of 69 patients diagnosed with cataract after treatment, 51 (73.9%) were characterised as radiation-related. Death from metastatic uveal melanoma occurred in 20.8% of the cohort, with a median follow-up of 10.1 years. Conclusions: Patients treated with PBI using a light field set-up technique experience good outcomes after irradiation. Eye preservation and retention of good VA are seen in the majority of cases, and tumour recurrence is low.